Sex-Specific Associations Between Oral Function Impairment and Clinical Outcomes in Hospitalized Older Adults: A Retrospective Observational Study - Lee YY; Weng SC; Lee YS; Chou YY; Kuo FH; Yang SH; Yeh YH; Chu WM; Hsu CY; Lin SY; Lin CF (Clinical Interventions in Aging)
Yen-Yang Lee,1 Shuo-Chun Weng,1– 5 Yu-Shan Lee,1,6 Yin-Yi Chou,1,7 Fu-Hsuan Kuo,1– 3,6 Shu-Hui Yang,8 Ya-Hui Yeh,8 Wei-Min Chu,2– 4,9 Chiann-Yi Hsu,10 Shih-Yi Lin,1– 4,11,* Cheng-Fu Lin2,3,12,* 1Center for Geriatrics and Gerontology, Taichung Veterans General Hospital, Taichung, Taiwan; 2Geriatrics and Gerontology Research Center, College of Medicine, National Chung Hsing University, Taichung, Taiwan; 3Department of Post-Baccalaureate Medicine, College of Medicine, National Chung Hsing University, Taichung, Taiwan; 4Institute of Clinical Medicine, School of Medicine, National Yang Ming Chiao Tung University, Taipei, Taiwan; 5Division of Nephrology, Department of Internal Medicine, Taichung Veterans General Hospital, Taichung, Taiwan; 6Department of Neurology, Neurological Institute, Taichung Veterans General Hospital, Taichung, Taiwan; 7Division of Allergy, Immunology and Rheumatology, Department of Internal Medicine, Taichung Veterans General Hospital, Taichung, Taiwan; 8Department of Nursing, Taichung Veterans General Hospital, Taichung, Taiwan; 9Department of Family Medicine, Taichung Veterans General Hospital, Taichung, Taiwan; 10Biostatistics Group, Department of Medical Research, Taichung Veterans General Hospital, Taichung, Taiwan; 11Division of Endocrinology and Metabolism, Department of Internal Medicine, Taichung Veterans General Hospital, Taichung, Taiwan; 12Health Management Center, Taichung Veterans General Hospital, Taichung, Taiwan*These authors contributed equally to this workCorrespondence: Shih-Yi Lin, Center for Geriatrics and Gerontology, Taichung Veterans General Hospital, Taichung, Taiwan, 1650 Taiwan Boulevard Sect. 4, Taichung, 407219, Taiwan, Tel +886-4-2359-2525 #83497, Fax +886-4-2359-5046, Email sylin@vghtc.gov.tw Cheng-Fu Lin, Health Management Center, Taichung Veterans General Hospital, Taichung, Taiwan, 1650 Taiwan Boulevard Sect. 4, Taichung, 407219, Taiwan, Tel +886-4-2359-2525 #83497, Fax +886-4-2359-5046, Email chengfue@gmail.comPurpose: Oral functional impairment is a critical factor influencing clinical outcomes in hospitalized older adults. Notably, sex disparities in oral health on clinical outcomes remain an often underappreciated aspect.This study aims to investigate the association between oral function, assessed using the bedside oral examination (BOE), and in-hospital mortality, with an emphasis on sex-specific differences.Patients and Methods: A retrospective cohort study was conducted involving 1,141 patients aged 65 years and older who were admitted to a medical center in Taiwan between 2018 and 2023. The BOE was a standardized clinical tool that evaluated eight domains of oral health, including swallowing, lips, tongue, saliva, mucous membranes, gingiva, teeth or dentures, and oral odor. Patients were classified into normal, moderate, or severe oral impairment groups. Cox proportional hazards models and Kaplan–Meier survival analysis were used to examine mortality risk, with results stratified by sex.Results: Overall, greater oral functional impairment was associated with higher in-hospital mortality and poorer physical, nutritional, and psychological status. In the sex-stratified analysis, severe oral impairment remained an independent predictor of mortality in male patients (hazard ratio 1.77, 95% confidence interval 1.05 to 2.99, p = 0.032), but not in female patients. Survival differences were statistically significant among men based on oral function levels, as shown by Kaplan–Meier curves (log-rank p = 0.014), while no significant difference was found among women (log-rank p = 0.376).Conclusion: Severe oral functional impairment significantly predicts in-hospital mortality among older men, but not women. These findings underscore the importance of sex-specific approaches to risk assessment and intervention. Incorporating oral health screening into routine geriatric care, especially for men, may enhance early identification of high-risk patients and inform targeted strategies to improve clinical outcomes. Further research is warranted to understand the mechanisms underlying these sex differences.Keywords: oral health, sex differences, in-hospital mortality, comorbidity, geriatrics, survival analysis